Two new species of Magnolia (Magnoliaceae) from Alta Verapaz and Quiché, Guatemala - Vázquez-García, J. Antonio; Tribouillier-Navas, Erick; Archila, Fredy; Aguilar, Rudy Eduardo; Shalisko, Viacheslav (Phytotaxa, 2022)
Two new species of Magnolia from Guatemala are described and illustrated, one belonging to Magnolia sect. Magnolia, M. weerakitana from Alta Verapaz Department, and the other to Magnolia sect. Talauma, M. quichensis, from Quiché Department. Magnolia lacandonica is first recorded for the flora of Guatemala. In this contribution, the number of native species of the genus for Guatemala increased from 15 to 18 species, occupying fourth place in the diversity of species of the genus in the Neotropics. We provide a map for magnolias for the Departments and an updated key to Guatemalan magnolias. The status of the two new species is proposed as endangered (EN) and as critically endangered (CR) according to IUCN criteria.